Resistência de Chrysodeixis includens (Lepidoptera: noctuidae) à inseticidas: levantamento, herança e custo adaptativo - Stacke, Regis Felipe (2020)
Chrysodeixis includens (Walker, 1858) (Lepidoptera: Noctuidae), is an important pest of soybean and cotton in Brazil. The use of insecticides is one of the main control tactics against this pest. To support Integrated Pest Management (IPM) and Insect Resistance Management (IRM) programs, in the first study, we characterized the susceptibility of Brazilian populations of C. includens to insecticides and; in the second study, we selected a strain with resistance to lambda-cyhalothrin and evaluated the inheritance, fitness costs and cross-resistance to other pyrethroids. In the first study, field populations were collected from soybean fields during the 2016–2017 and 2017–2018 crop seasons. In the laboratory, late L2/early L3 larvae were exposed to insecticides in diet-overlay or topical bioassays. Field populations of C. includens showed low levels of resistance to spinetoram (LC50 = 0.074 to 0.25 μg a.i. cm-2 ), indoxacarb (LC50 = 0.46 to 0.94 μg a.i. cm-2 ), thiodicarb (LC50 = 9.14 to 36.61 μg a.i. cm-2 ), chlorantraniliprole (LC50 = 0.15 to 0.57 μg a.i. cm-2 ), flubendiamide (LC50 = 0.45 to 2.01 μg a.i. cm-2 ), and chlorfenapyr (LC50 = 0.15 to 0.25 μg a.i. cm-2 ); the resistance ratios (RR) were less than 16-fold. In contrast, C. includens populations showed high levels of resistance to lambda-cyhalothrin (LC50 = 3.71 to 9.54 μg a.i. cm-2 ), methoxyfenozide (LC50 = 0.67 to 4.23 μg a.i. cm-2 ), novaluron (LC50 = 27.52 to 77.63 μg a.i. cm-2 ), and teflubenzuron (LC50 = 13.41 to 73.02 μg a.i. cm-2 ). The RRs relative to a susceptible population was up to 62.5-, 63-, 1,553- and 5,215-fold, respectively. Based on the second study, estimated LD50 values of lambda- cyhalothrin for the susceptible and resistant strains were 0.0015 and 0.11 μg a.i. larva-1 , respectively, representing a resistance ratio (RR) of 73.3-fold. The LD50 values of heterozygous were 0.016 and 0.017 μg a.i. larva-1 , indicating an autosomal inheritance of resistance. On lambda-cyhalothrin sprayed-leaves, the resistant strain showed > 85% survival. By contrast, heterozygous and susceptible strains had < 64 and 8% survival, respectively, indicating an incompletely dominant resistance at the field dose of lambda-cyhalothrin. The resistant strain also showed cross-resistance to deltamethrin (RR = 6.2-fold) and cypermethrin (RR = 22.5- fold). Fitness costs studies showed that resistant insects had 71 and 48% lower survival until adult and reproductive rates, respectively, when compared to the Sus strain. Thus, the selection of a C. includens strain resistant to lambda-cyhalothrin showed that resistance inheritance patterns were autosomal, incompletely dominant and associated with substantial fitness costs. The results presented here support the IPM and IRM programs for C. includens in Brazil.